Pregunta
Solve the equation and simplify your answer. \( \begin{array}{c}-4(3+x)+5=4(x+3) \\ x=-\frac{[?]}{}\end{array} \)
Ask by Rose Pollard. in the United States
Feb 04,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( x = -\frac{19}{8} \)
Solución
Solve the equation \( -4(3+x)+5=4(x+3) \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(-4\left(3+x\right)+5=4\left(x+3\right)\)
- step1: Calculate:
\(-7-4x=4\left(x+3\right)\)
- step2: Calculate:
\(-7-4x=4x+12\)
- step3: Move the expression to the left side:
\(-7-4x-\left(4x+12\right)=0\)
- step4: Calculate:
\(-19-8x=0\)
- step5: Move the constant to the right side:
\(-8x=0+19\)
- step6: Remove 0:
\(-8x=19\)
- step7: Change the signs:
\(8x=-19\)
- step8: Divide both sides:
\(\frac{8x}{8}=\frac{-19}{8}\)
- step9: Divide the numbers:
\(x=-\frac{19}{8}\)
The solution to the equation is \( x = -\frac{19}{8} \) or \( x = -2.375 \).
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Bonus Knowledge
To solve the equation \(-4(3+x)+5=4(x+3)\), let's first simplify both sides. Starting with the left side: \[ -4(3+x) + 5 = -12 - 4x + 5 = -4x - 7. \] Now, for the right side: \[ 4(x+3) = 4x + 12. \] Setting both sides equal gives us: \[ -4x - 7 = 4x + 12. \] Next, we want to combine like terms: \[ -4x - 4x = 12 + 7 \implies -8x = 19. \] Now, divide both sides by -8: \[ x = -\frac{19}{8}. \] So, the solution is: \[ x = -\frac{19}{8}. \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium